THE IMPACTS OF FOREIGN DIRECT INVESTMENT TO THE ENVIRONMENT IN DEVELOPING COUNTRIES: INDONESIAN PERSPECTIVE - Wartini, Sri (Indonesian Journal of International Law, 2016)
Foreign Direct Investment (FDI) may cause positive and negative impacts in developing countries, such as in Indonesia. The positive impact of FDI may enhance economic growth in developing countries, on the other hand, negative impacts of FDI may cause environmental pollution and environmental degradation. FDI in Indonesia has already increased economic growth, however, the environmental degradation and environmental pollution cannot be avoided. In certain extent, in order to gain a great profit, FDI can be used by the foreign investor to violate human rights and the environment in the host states. Unfortunately, the government in developing countries often sacrifice the interest of environment to booast economic growth. Hence, it is crucial to have a good policy in FDI as well as environmental protection. State needs to balance the interest of environment and economic growth, since both of them are interdependence. The existence of FDI shall not hinder the political will of the house state to protect the environment. However, it is essential to enhance the role of the host state government to have a good policy of FDI in order to protect the environment. The paper undertakes a critical examination of the issues relating to the impacts of FDI to the protection of environment in Indonesia. Furthermore, it also analizes the challenges and opportunities to enhance environmental protection. The research method of this article is qualitative and the approach of the research is normative. The research finds that the role of the host sate to have agood policy in FDI as well as protection of the environment is paramount.